Polygyny, oviposition, life cycle and longevity of the three subspecies of leaf-cutting ants, Acromyrmex subterraneus (Hymenoptera: Formicidae) - Forti, Luiz Carlos [UNESP]; Camargo, Roberto da Silva [UNESP]; Protti de Andrade, Ana Paula [UNESP]; Caldato, Nadia [UNESP]; Sousa, Kátia Kaelly Andrade [UNESP]; Silva, Aline de Amorim Costa da; Ramos, Vânia Maria (Taylor & Francis, 2018)
Research related to the comparative biology of phylogenetically close ant species has received little attention, although it is the basis for understanding the systematics of some sibling groups. The objective was to study the polygyny, oviposition, life cycle and longevity of the three subspecies of leaf-cutting ants. For that, we studied: oviposition rate – queens from three colonies were individually placed in plastic containers, and at 24-hour intervals, the laid eggs were quantified over a period of 96 hours; the workers’ life cycle – the development of immature ants was observed every 24 hours and, as a result, the duration of each stage of development was determined; the workers’ longevity – newly emerged adults were tagged and returned to the fungus chamber of their respective nests, and daily observations were made in each of the nest’s chamber. Laying rates were variable in the three queens studied, with a mean of total eggs laid of 271 for Acromyrmex subterraneus brunneus, 113 for Acromyrmex subterraneus subterraneus and 119 for Acromyrmex subterraneus molestans.The incubation period was 21.2 days in A. s. brunneus, 22.8 days in A. s. subterraneus and 20.4 days in A. s. molestans. The larval phase and pupal phase lasted on average 22.5 and 21.2 days in A. s. brunneus, 22.8 and 15.8 days in A. s. subterraneus and 17.2 and 14.2 days in A. s. molestans, respectively. Life cycle was different in the studied taxa, from 62 to 77 days in A. s. brunneus, from 59–68 days in A. s. subterraneus and from 51 to 55 days in A. s. molestans. The workers’ longevity varied between subspecies A. s. brunneus, A. s. subterraneus and A. s. molestans.
Keywords: Acromyrmex subterraneus brunneus; Acromyrmex subterraneus molestans; Acromyrmex subterraneus subterraneus; leaf-cutting ants; life cycle; oviposition; workers’ longevity